Biochemical evidence for minimal vegetation change in peatlands of the West Siberian Lowland during the Medieval Climate Anomaly and Little Ice Age. Issue 5 (12th May 2014) - Philben, Michael; Kaiser, Karl; Benner, Ronald
Abstract Peatland vegetation is controlled primarily by the depth of the water table, making peat paleovegetation a useful climate archive. We applied a biochemical approach to quantitatively estimate the plant sources of peat carbon based on (1) neutral sugar compositions of Sphagnum, vascular plants, and lichens and (2) lignin phenol compositions of vascular plants. We used these biochemical indices to characterize vegetation change over the last 2000 years in four peat cores from the West Siberian Lowland (Russia) to investigate climate change during the Medieval Climate Anomaly and Little Ice Age. The vegetation was dominated by Sphagnum in all four cores, but was punctuated by several rapid but transient transitions to vascular plant dominance in the two cores from the southern West Siberian Lowland (<60°N latitude). Lichen contributions were evident at the end of the Medieval Climate Anomaly and during the Little Ice Age in the two cores from northern West Siberian Lowland (>60°N), possibly indicating permafrost development. However, there was no evidence for sustained vegetation change in response to either climatic event in cores from southern West Siberian Lowland. This suggests that these climatic events were relatively mild in the southern West Siberian Lowland, although the sensitivity of bog plant communities to climate change remains poorly understood.